Effects of a fermented goat milk with Lactobacillus in a diet-induced obesity murine model - Márquez, María Antonela (2021)
The use of nutritional therapies with functional foods has a promising application for metabolic disorders, such as diet-induced obesity (DIO). The objective of this work was to evaluate in mice with DIO, the administration of fermented goat milk (FGM) with Lactobacillus (L.) delbrueckii subsp. bulgaricus CRL1447 and supplemented with different mixes of Lactobacillus strains, on metabolic and immunologic parameters. The strain mixtures (Mix) were formed as follow: Mix 1: L. fermentum CRL1446, L. plantarum CRL1449 and CRL1472 strains, Mix 2: CRL1446 and CRL1449, Mix 3: CRL1446 and CRL1472 and Mix 4: CRL1449 and CRL1472. Seven groups (n = 6) of male C57BL/6 mice were used: Control groups: 1) Standard diet (SD) group: SD + water, 2) FGM group: SD + FGM; 3) Obese (Ob)+FGM group: high fat diet (HFD) + FGM; Obese groups with treatments: 4) Ob+FGM+Mix1 group: HFD + FGM + Mix1, 5) Ob+FGM+Mix2 group: HFD + FGM + Mix2, 6) Ob+FGM+Mix3 group: HFD + FGM + Mix3, 7) Ob+FGM+Mix4 group: HFD + FGM + Mix4. After 10 weeks of feeding, following determinations were made in plasma: glucose and lipid profile by enzymatic methods, leptin by ELISA and cytokines by CBA. Body weight gain (BWG) was evaluated weekly. The results were compared with Ob+FMG group. BWG decreased 34% and 22% in Ob+FGM+Mix2 and Ob+FGM+Mix3 group (respectively). Triglyceride and leptin levels in Ob+FGM+Mix2 group were significantly reduced (35% and 22%, respectively). Regarding total and LDL cholesterol, no significant differences were observed in the different treatment groups. HDL-cholesterol values increased 22% in FGM+Mix 2 and 19% in FGM+Mix3. Levels of glucose values decreased in groups fed with FGM+Mix2 (48%) and FGM+Mix3 (43%). The administration of supplementated FGM with Mix2 reduce levels of pro-inflammatory cytokines (MCP-1 and IL-6), while no significant differences were observed in levels of anti-inflammatory cytokine IL-10. In conclusion, we suggest the use of FGM supplemented with Mix2 as a supplement to nutritional therapies due to its hypotriglyceridemic, hypoglycemic and immunomodulatory properties.